Acute day units in non-residential settings for people in mental health crisis: the AD-CARE mixed-methods study - David Osborn; Danielle Lamb; Alastair Canaway; Michael Davidson; Graziella Favarato; Vanessa Pinfold; Terry Harper; Sonia Johnson; Hameed Khan; James Kirkbride; Brynmor Lloyd-Evans; Jason Madan; et al. (National Institute for Health Research, 2021)
Background: For people in mental health crisis, acute day units provide daily structured sessions and peer support in non-residential settings as an alternative to crisis resolution teams. Objectives: To investigate the provision, effectiveness, intervention acceptability and re-admission rates of acute day units. Design: Work package 1 - mapping and national questionnaire survey of acute day units. Work package 2.1 - cohort study comparing outcomes during a 6-month period between acute day unit and crisis resolution team participants. Work package 2.2 - qualitative interviews with staff and service users of acute day units. Work package 3 - a cohort study within the Mental Health Minimum Data Set exploring re-admissions to acute care over 6 months. A patient and public involvement group supported the study throughout. Setting and participants: Work package 1 - all non-residential acute day units (NHS and voluntary sector) in England. Work packages 2.1 and 2.2 - four NHS trusts with staff, service users and carers in acute day units and crisis resolution teams. Work package 3 - all individuals using mental health NHS trusts in England. Results: Work package 1 - we identified 27 acute day units in 17 out of 58 trusts. Acute day units are typically available on weekdays from 10 a.m. to 4 p.m., providing a wide range of interventions and a multidisciplinary team, including clinicians, and having an average attendance of 5 weeks. Work package 2.1 - we recruited 744 participants (acute day units, n = 431; crisis resolution teams, n = 312). In the primary analysis, 21% of acute day unit participants (vs. 23% of crisis resolution team participants) were re-admitted to acute mental health services over 6 months. There was no statistically significant difference in the fully adjusted model (acute day unit hazard ratio 0.78, 95% confidence interval 0.54 to 1.14; p = 0.20), with highly heterogeneous results between trusts. Acute day unit participants had higher satisfaction and well-being scores and lower depression scores than crisis resolution team participants. The health economics analysis found no difference in resource use or cost between the acute day unit and crisis resolution team groups in the fully adjusted analysis. Work package 2.2 - 36 people were interviewed (acute day unit staff, n = 12; service users, n = 21; carers, n = 3). There was an overwhelming consensus that acute day units are highly valued. Service users found the high amount of contact time and staff continuity, peer support and structure provided by acute day units particularly beneficial. Staff also valued providing continuity, building strong therapeutic relationships and providing a variety of flexible, personalised support. Work package 3 - of 231,998 individuals discharged from acute care (crisis resolution team, acute day unit or inpatient ward), 21.4% were re-admitted for acute treatment within 6 months, with women, single people, people of mixed or black ethnicity, those living in more deprived areas and those in the severe psychosis care cluster being more likely to be re-admitted. Little variation in re-admissions was explained at the trust level, or between trusts with and trusts without acute day units (adjusted odds ratio 0.96, 95% confidence interval 0.80 to 1.15). Limitations: In work package 1, some of the information is likely to be incomplete as a result of trusts' self-reporting. There may have been recruitment bias in work packages 2.1 and 2.2. Part of the health economics analysis relied on clinical Health of the Nations Outcome Scale ratings. The Mental Health Minimum Data Set did not contain a variable identifying acute day units, and some covariates had a considerable number of missing data. Conclusions: Acute day units are not provided routinely in the NHS but are highly valued by staff and service users, giving better outcomes in terms of satisfaction, well-being and depression than, and no significant differences in risk of re-admission or increased costs from, crisis resolution teams. Future work should investigate wider health and care system structures and the place of acute day units within them; the development of a model of best practice for acute day units; and staff turnover and well-being (including the impacts of these on care). Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 9, No. 18. See the NIHR Journals Library website for further project information.